The Influence Of E-Commerce And Digital Payments On The Income Of Micro, Small, And Medium Enterprises (Msmes) In Bengkulu City - Andestar, Tomi; Yanti , Rina Trisna; Yustanti, Nirta Vera (Utami Publisher, 2025)
This study aims to analyze the influence of e-commerce and digital payment systems on the revenue of Micro, Small, and Medium Enterprises (MSMEs) in Bengkulu City. This study used a quantitative associative approach with a survey method involving 100 MSME respondents who utilize e-commerce platforms and digital payment services. Data were collected using a questionnaire and analyzed through multiple linear regression with SPSS to test the partial and simultaneous effects of independent variables on MSME revenue. Based on data from 100 MSME respondents, a multiple linear regression analysis yielded a coefficient of determination (R²) of 0.526, indicating that variations in MSME revenue can be explained by e-commerce and digital payments. The results of this study indicate that e-commerce and digital payments, both partially and simultaneously, have a positive and significant influence on MSME revenue.